1990
DOI: 10.1002/bjs.1800771112
|View full text |Cite
|
Sign up to set email alerts
|

Development and reversibility of T lymphocyte dysfunction in experimental obstructive jaundice

Abstract: This study evaluates the effect of experimental biliary obstruction by bile duct ligation (BDL) and biliary drainage on cell-mediated immunity in Wistar rats. Immune status has been assessed by a mitogen stimulation test of T lymphocytes with phytohaemagglutinin. Animals were followed for up to 35 days after BDL. Regression analysis showed a significant negative correlation between lymphocyte function and the period of jaundice (correlation coefficient -0.57, P less than 0.001). Following BDL for 21 days, grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…The detailed mechanism of suppressed Tlymphocyte proliferation is unclear (13,18). Various plasma circulating inhibitory factors such as bile acids, cytokine, bilirubin, endotoxin, and lipoproteins are possible causes of T-lymphocyte defects (19). High serum bile acids have been shown to inhibit lymphocyte proliferation in a previous study (20).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanism of suppressed Tlymphocyte proliferation is unclear (13,18). Various plasma circulating inhibitory factors such as bile acids, cytokine, bilirubin, endotoxin, and lipoproteins are possible causes of T-lymphocyte defects (19). High serum bile acids have been shown to inhibit lymphocyte proliferation in a previous study (20).…”
Section: Discussionmentioning
confidence: 99%
“…Deitch et al [1,2,22] and Thompson et al [23] reported that bacterial translocation from the gut impairs systemic cell-mediated immunity. The immune state of the CBD ligated mice could influence their susceptibility to bacterial translocation, and loss of intestinal barrier function results in a state of acquired systemic immune suppression in obstructive jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of bile into the normal enterohepatic circulation resulted in reduced rates of postoperative death [8], endotoxaemia [9], and renal impairment [10], more rapid recovery of cell-mediated immunity [11], and better regeneration rate of liver cells after hepatectomy [12]. …”
Section: Experimental Studiesmentioning
confidence: 99%